Live More Prosperously By Enjoying Old Age Using Pension Funds - Pigai, Owaada (Institut Manajemen Wiyata Indonesia, 2024)
In this research method I took a case study at PT. Taspen Surabaya is based on article 58 of Law Number 11 of 1992 concerning pension funds which explains that anyone is prohibited from intentionally causing the payment of an amount of money to the Pension Fund that deviates from the regulations and participating in transactions involving an increase in pension funds. PT. Taspen is an initial service before the customer recipient is confirmed as a Pension Fund recipient. In the articles that I have written, everything is based on case studies that I have conducted, namely using the interview method. The results and discussions show the organizational structure of PT. Taspen Surabaya as well as services provided to civil servants, including work accident insurance programs. This program includes protection against the risk of work accidents in the form of treatment, compensation, and disability benefits. In addition, a pension insurance (ENT) program is included, which is related to retirement age and death insurance.